Supraglottic laryngeal lymphomatoid granulomatosis in an immunocompetent patient: a case report - Harvey-Bolduc, Simon-Pierre; Guay, Benoit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Lymphomatoïd granulomatosis is a rare lymphoproliferative disease caused by Epstein-Barr virus described in 1972 by Liebow. The most common primary localization is the lungs. Other systems are affected occasionally such as the skin, central nervous system, renal and gastrointestinal system. Some cases have been described at the laryngeal level in immunosuppressed patients. This is a case report of supraglottic lymphomatoid granulomatosis in an immunocompetent patient. A literature review on lymphomatoid granulomatosis will be detailed and the clinical case will be described including investigations, treatment and follow-up. The differential diagnosis of this pathology as well as the importance of histopathology will also be discussed. Several radiological imaging and histopathology slides will be presented. Emphasis will be placed on the difficulty of diagnosis given the frequent multisystem involvement and on the importance of the multidisciplinary team approach including otolaryngology, haematology-oncology, nephrology, pathology and radiology. We will end with a discussion about the case with reference to the current literature on the subject.